International Telecommunication Union-Radiocommunication Sector P.837-6 and P.837-7 performance to estimate Indonesian rainfall - Marzuki Marzuki; Dea Kurnia Harysandi; Rini Oktaviani; Lisna Meylani; Mutya Vonnisa; Harmadi Harmadi; Hiroyuki Hashiguchi; Toyoshi Shimomai; L. Luini; Sugeng Nugroho; Muzirwan Muzirwan; Nor Azlan Mohd Aris (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
This work evaluated the performance of International Telecommunication Union-Radiocommunication Sector (ITU-R) P.837-6 and P.837-7 models (Annex 1) to estimate one-minute rainfall rates in Indonesia. In addition to the default ITU-R P.837-6, the input of ITU-R P.837-6 is also modified using data which has better spatial resolution, i.e. a combination of Tropical Rainfall Measuring Mission (TRMM) 3A25 and 3B43 (ITU-R+3A25+3B43), 3B42 and 3B43 (ITU-R+3B42+3B43), Global Satellite Mapping of Precipitation (ITU-R+GSMaP), and Global Precipitation Measurement (ITU-R+GPM). Among the five test sites, the default ITU-R P.837-6 and ITU-R+3A25+3B43 could predict one-minute rainfall rates at two locations accurately. The ITU-R P.837-7 exhibited a marginally better performance for sites that had a high percentage of very heavy rain, particularly at large (1%) and small (0.001%) percentages of time exceeded. The spatial distribution of rainfall rate produced by ITU-R P.837-7 and ITU-R+3A25+3B43 was closer to the pattern demonstrated by recent satellite precipitation measurements.